PERBEDAAN PENGARUH KB SUNTIK DEPO MEDROXI PROGESTERON ASETAT (DMPA) DENGAN KB IMPLAN TERHADAP GANGGUAN MENSTRUASI DI WILAYAH KERJA PUSKESMAS 1 PURWONEGORO KABUPATEN BANJARNEGARA TAHUN 2011 - Laely, Fitriatun Nur; Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Menstrual disorders are the most common complaint by the acceptors of hormonal especially those that contain progestins hormony as KB mini pil, injections Depo Medroksi Progesteron Asetat (DMPA) and implants. Reggular menstrual KB mini pil whereas KB implants have fewer complaints of menstrual disorders than injecting DMPA. Purwonegoro sub district has the most hormonal acceptor in the Banjarnegara District. Determine the effect of menstrual disorders difference between mothers who use injectable contraceptive DMPA with contraceptive implant in a work area health center 1 Purwonegoro Banjarnegara District in 2011. This research is an observational study using cross-sectional design. The number of samples injectable DMPA acceptors 98 people and Implants acceptors Â 81 people use systematic random sampling. Methods of data analysis in this study using Chi Square. Acceptors injection at a work area health center 1 Purwonegoro Banjarnegara District in 2011 is 98 people (54,7%) more than acceptors implant that is 81 people (53,3%). Acceptors of injectable DMPA most experienced menstrual disorders (84,7%). Acceptor implant most experienced menstrual disorders (65,4%). There are differences in the influence of menstrual disorders among women who use contraceptive implants with injectable contraceptive DMPA in a work area health center 1 Purwonegoro Banjarnegara District in 2011 (p = 0.003). There is a difference in the influence of menstrual disorders among women who use contraceptive implants with injectable contraceptive DMPA. Suggestion: Midwives should in providing counseling to prospective acceptors be more emphasis about the side effects menstrual disorders of each contraceptives so prospective acceptors can choose appropriate contraception condition. Keywords: Implant, DMPA, Menstrual disorders